Market orientation and planning flexibility in SMEs - Performance implications and an empirical investigation - Alpkan, Lutfihak; Yilmaz, Cengiz; Kaya, Nihat (Sage Publications Ltd, 2007)
The study examines the joint effects of market orientation (an internal, cultural factor) and planning flexibility (an internal, process factor) on business performance in small and medium-sized firms. In addition, the conceptual model incorporates market dynamism (an external factor) as a moderator on business performance. A number of hypothesized relationships are tested with a sample of small and medium-sized manufacturing firms in Turkey. The results suggest that while, in general, both market orientation and planning flexibility positively influence firm performance, contrary to the author's hypothesis, planning flexibility exerts a negative effect on performance in highly dynamic markets. Theoretical and managerial implications of these and other findings are discussed.
Keywords: market dynamism; market orientation; planning flexibility; small and medium-sized enterprises